Exploring domestication pattern in lotus: insights from dispensable genome assembly - Qi, Huanhuan; Yu, Feng; Lü, Shiyou; Damaris, Rebecca Njeri; Dong, Guoqing; Yang, Pingfang (Frontiers in Plant Science, 2023)
Lotus (Nelumbo nucifera Gaertn.), an important aquatic plant in horticulture and ecosystems, has been cultivated for more than 7000 years and domesticated into three different subgroups: flower lotus (FL), rhizome lotus (RL), and seed lotus (SL). To explore the domesticated regions of each subgroup, re-sequencing data of 371 lotus accessions collected from the public database were aligned to the genome (v3) of 'China-Antique (CA)'. Unmapped reads were used to build the dispensable genome of each subgroup using a metagenome-like assembly strategy. More than 27 Mb of the dispensable genome in these three subgroups and the wild group was assembled, of which 11,761 genes were annotated. Some of the contigs in the dispensable genome were similar to the genomic segments of other lotus accessions other than 'CA'. The annotated genes in each subgroup played essential roles in specific developmental processes. Dissection of selective signals in three cultivated subgroups also demonstrated that subgroup-specific metabolic pathways, such as the brassinosteroids metabolism enrichment in FL, associated with these selected genes in each subgroup and the contigs in dispensable genome nearly located in the domesticated regions of each subgroup, respectively. Our data presented a valuable resource for facilitating lotus genomic studies, complemented the helpful information to the reference genome, and shed light on the selective signals of domesticated subgroups.